1995
DOI: 10.1128/aem.61.11.3865-3871.1995
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Plant Growth Promotion of Detergent-Adapted Pseudomonas fluorescens ANP15 and Pseudomonas aeruginosa 7NSK2

Abstract: Four detergents were tested as selective C sources for the plant growth-promoting rhizobacteria Pseudomonas aeruginosa 7NSK2 and Pseudomonas fluorescens ANP15. CO-720 (Igepal CO-720) or DOS (dioctyl sulfosuccinate), applied at 0.2% to the soil, increased the number of detergent-adapted, inoculated strains by almost 1.5 log units after 25 days, accounting for virtually the entire increase in total bacteria. The same dose of Tween 80 or N-laurylsarcosine, on the other hand, increased the indigenous populations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Strategies that may facilitate improved control of the biomass and distribution of indigenous and introduced microorganisms can be broadly grouped into those that involve rhizodeposits and those that do not. Approaches that fall into the latter category include attempts to select for specific microbial groups by applying chemical amendments to soils (Devliegher et al , 1995), modifications to proteins in rhizodermal cell membranes involved in plant–microorganism signalling (Samaj et al , 1999), and changes to root growth and architecture. These strategies are largely beyond the scope of this review (see Ryan et al , 2009 for detailed information); however, some may be very effective.…”
Section: Implications Of and Potential Mechanisms To Adjust Microbialmentioning
confidence: 99%
“…Strategies that may facilitate improved control of the biomass and distribution of indigenous and introduced microorganisms can be broadly grouped into those that involve rhizodeposits and those that do not. Approaches that fall into the latter category include attempts to select for specific microbial groups by applying chemical amendments to soils (Devliegher et al , 1995), modifications to proteins in rhizodermal cell membranes involved in plant–microorganism signalling (Samaj et al , 1999), and changes to root growth and architecture. These strategies are largely beyond the scope of this review (see Ryan et al , 2009 for detailed information); however, some may be very effective.…”
Section: Implications Of and Potential Mechanisms To Adjust Microbialmentioning
confidence: 99%
“…Ecological selectivity can also be based on the use of a specific substrate which is unavailable to a majority of other soil microorganisms. Devliegher et al (41) showed the effectiveness of this principle, in the use of a combined addition of specific detergents as carbon sources and detergentdegradative Pseudomonas spp. added to soil.…”
Section: Ecological Selectivitymentioning
confidence: 99%
“…In all cases the success of inoculation is greatly influenced by the number of viable cells introduced into soil [4,5]. One way to enhance the efficacy of inoculation is to improve the growth of the introduced microbial population using nutrient amendments [6,7]. Nutrient amendment can stimulate the growth of bacterial inocula but a large amount of carbon source is often required.…”
Section: Introductionmentioning
confidence: 99%